2021
DOI: 10.1002/ajmg.c.31956
|View full text |Cite
|
Sign up to set email alerts
|

Throat and voice problems inEhlers–Danlossyndromes and hypermobility spectrum disorders

Abstract: A small number of case reports and observational studies describe chronic nasal congestion, upper airway obstruction, dysphonia, vocal cord abnormalities, and swallowing abnormalities in the Ehlers-Danlos syndromes. Little is known of the causes and therefore treatments of these, yet they are not uncommon findings in persons with hypermobility-related conditions presenting in the healthcare setting. We have a specialist multidisciplinary ear, nose, and throat and speech therapy practice with accumulating obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…As the largest study of its kind in terms of exploring throat symptoms of EDS/HSD and self‐management strategies, this work provides a unique and valuable contribution and has generated interest from leading health care practitioners specializing in EDS and HSD. Prior to this study, throat symptoms of EDS/HSD have not been well reported or characterized 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the largest study of its kind in terms of exploring throat symptoms of EDS/HSD and self‐management strategies, this work provides a unique and valuable contribution and has generated interest from leading health care practitioners specializing in EDS and HSD. Prior to this study, throat symptoms of EDS/HSD have not been well reported or characterized 20 …”
Section: Discussionmentioning
confidence: 99%
“…mechanisms by which one's voice may be affected. 20 As the largest study of its kind in terms of exploring throat symptoms of EDS/HSD and self-management strategies, this work provides a unique and valuable contribution and has generated interest from leading health care practitioners specializing in EDS and HSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with altered voice, deep neck pains, choking, and swallowing problems may also benefit from voice therapy, which is a low-risk treatment option. 6,7 Beyond PT/ OT, patients may seek out alternative methods of exercise and movement depending on their tolerance. Gentle movement techniques that encourage efficient movement and well-being include Alexander technique, Feldenkrais, tai chi, and qigong.…”
Section: Movementmentioning
confidence: 99%
“…In addition, some patients may experience benefits from neurologic, orthopedic, or pelvic floor PT. Patients with altered voice, deep neck pains, choking, and swallowing problems may also benefit from voice therapy, which is a low-risk treatment option 6,7. Beyond PT/OT, patients may seek out alternative methods of exercise and movement depending on their tolerance.…”
Section: Movementmentioning
confidence: 99%